Imagining the Dead in British Literature and Culture, 1790-1848 - McAllister, David (Springer International Publishing, 2018)
This book offers the first account of the dead as an imagined community in the early nineteenth-century. It examines why Romantic and Victorian writers (including Wordsworth, Dickens, De Quincey, Godwin, and D'Israeli) believed that influencing the imaginative conception of the dead was a way to either advance, or resist, social and political reform. This interdisciplinary study contributes to the burgeoning field of Death Studies by drawing on the work of both canonical and lesser-known writers, reformers, and educationalists to show how both literary representation of the dead, and the burial and display of their corpses in churchyards, dissecting-rooms, and garden cemeteries, responded to developments in literary aesthetics, psychology, ethics, and political philosophy. Imagining the Dead in British Literature and Culture, 1790-1848 shows that whether they were lauded as exemplars or loathed as tyrants, rendered absent by burial, or made uncannily present through exhumation and display, the dead were central to debates about the shape and structure of British society as it underwent some of the most radical transformations in its history. .